The Influence of Islamic Religious Education Student Organizations on Study Discipline at STAI Samora Pematangsiantar - Samroh Imtihani Nasution; Sri Wahyuni; Hendri Yahya Saputra (Edumaspul: Jurnal Pendidikan, 2024)
An organization is a social entity that has certain goals, a system of structured and coordinated activities, and is related to the external environment but is determined by identifiable boundaries. The aim of this research is to determine the influence of student organizational activity on learning discipline. The research method used is a quantitative method. The population in this study were students from the class of 2022, 2023 of the Islamic Education STAI Samora Pematangsiantar study program, totaling 52 respondents. The research instrument used was the distribution of questionnaires and documentation with data analysis using simple linear regression. The results of the research show that activeness in student organizations influences the learning outcomes of students at the Islamic Education STAI Samora Pematangsiantar study program. Based on the results of the descriptive analysis, activeness in organizations was classified as high, as many as 33 students (63.5%) were active in organizations, and learning discipline in participating in student organizations was classified as high as many as 30 students (57.6 %). From the results of the simple linear regression analysis, the constanta (a) value is 2.245 and the regression coefficient (b) value is 0.392 with the regression equation Y = 2.245+ 0.392 X. From the results of the simple linear regression analysis, there is a negative influence between activities in student organizations regarding learning outcomes, it can be concluded that the more activities one participates in in student organizations, the lower the learning outcomes will be. Judging from the R2 (R Square Change) calculation, the value obtained is 0.451. This means that the contribution of activities in student organizations to learning outcomes is 45.1%.